MOLECULAR DETECTION OF DRUG-RESISTANT GENES AMONG Clostridioides difficile FROM DIARRHEIC CHILDREN IN DUHOK CITY -IRAQ - Bakhtyar Nader Ali (Science Journal of University of Zakho)
Clostridioides difficile, formerly known as Clostridium difficile is the most common cause of antibiotic-associated diarrhea and colitis and is characterized by resistance to multiple drugs. This study amid to characterize antibiotic resistance genes in C. difficile among pediatric diarrheal cases from Duhok Governorate, Kurdistan regional Iraq, providing critical insights for regional infection control and treatment guidelines. Thirteen C. difficile-positive stool samples (from a cohort of 200 children aged between 6 months- 6 years) were analysed by PCR for detecting resistance genes CTX-M (cefotaxime), ermC (clindamycin), ere(A) (erythromycin), rdxA (metronidazole), vanR (vancomycin). The result illustrated that cefotaxime, CTX-M gene detected in 100% DNA samples, with high rates of resistance of clindamycin (ermC gene, 76.9%) and erythromycin (69.2%, ere(A) gene) while resistance to metronidazole (rdxA) and vancomycin resistance (vanR) remained rare (7,69% and 15.38%, respectively). Venn diagram analysis highlighted frequent co-occurrence of resistance to these genes, and six samples (46.2%) harbored three genes, CTX-M, ermC and ere (A), and also double other two samples harbored two genes, CTX-M and ermC and CTX-M and ere (A). In addition, one sample harbored only the CTX-M gene. This study underscores the prevalence of the alarming high rate of antibiotic resistance found in C. difficile among pediatric diarrheal cases such as against cefotaxime, clindamycin, and erythromycin. The persistence of susceptibility to vancomycin and metronidazole supports their continued use as first-line therapies for both community and hospital infections region